Speaking in other voices : an ethnography of Walloon puppet theaters - Gross, Joan (Pragmatics & beyond ;, 2001)
Linking actual instances of language use with structures of social power in francophone Belgium, Gross outlines the history and contemporary configuration of rod puppetry in Liège. The analysis of this working class performance art moves between what occurs on and off stage. As puppeteers speak in other voices, sometimes in Walloon and sometimes in French, they create a sociolinguistic model based on 19th century renditions of medieval texts, the voices of past puppeteers, and the language that surrounds them. The high level of linguistic reflexivity created by the regional language movement has led to frequent metalinguistic and metapragmatic commentaries within the puppet shows. This complex speech genre embedded in social context shows the influence of identity struggles: from local class oppositions to imperial designs abroad. Keeping a tight focus on language, Speaking in Other Voices examines the process of entextualization and recontextualization as stories of war and religion are transmitted to succeeding generations.